Active energy ray-curable composition for forming hard coat layer, and hard coat film and laminate using the same
Patent Information
- Application Number
- JP2023140236
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-30
AI Technical Summary
【0024】 本発明により、外部からの紫外線からディスプレイ表示部を保護し、白色鮮明度を向上させ、生産プロセス中の傷付き防止、硬化収縮によるカール防止および光透過性フィルムとの密着性を向上させるハードコート層形成用活性エネルギー線硬化型組成物、それを用いたハードコートフィルムおよびその積層体を提供することが出来る。
Smart Images

Figure 2025034077000001 
Figure 2025034077000002 
Figure 2025034077000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable composition for forming a hard coat layer, a hard coat film using the same, and a laminate thereof.
[0002] More specifically, the present invention relates to an active energy ray-curable composition for forming a hard coat layer, for obtaining a hard coat film that can be applied to displays such as TVs, notebook computers, mobile phones, smartphones, e-books, and electronic signage, a hard coat film using the same, and a laminate thereof. [Background technology]
[0003] In addition to liquid crystal displays (LCDs), which have long been widely used for display applications in TVs, laptops, mobile phones, smartphones, etc., various other displays have been developed, and products taking advantage of their various features are being introduced to the market.
[0004] Organic electroluminescence (EL) displays are one such example, and are rapidly expanding into a variety of applications including TVs and smartphones.
[0005] Compared to LCDs and OLED displays, which are strong when playing moving images, electronic paper has features for still image playback such as fast response time, high visibility, and the ability to retain displayed information even when the power is turned off or with very little power. In recent years, electronic paper has also become more colorized, and is being developed and commercialized for use in e-books, electronic signage, and other applications.
[0006] In display products, the adverse effects of external ultraviolet rays on display functions are a problem, which is particularly serious in outdoor applications. In order to prevent the effects of external ultraviolet rays, it is common to provide an ultraviolet ray cutoff layer on the outside of the functional layer to be protected. Furthermore, by providing an ultraviolet ray cut-off layer on the outer side of the functional layer to be protected, it is possible to protect the eyes from harmful ultraviolet rays generated from inside the display.
[0007] Display products, especially mobile devices such as laptops, mobile phones, smartphones, pads, smart watches, and e-books, are becoming lighter and smaller in size because of the emphasis on portability, and efforts are being made to multi-function and thin functional layers in the display configuration. In the study of thinning, progress is being made in reducing the thickness of base films, and thin films of 50 μm or less are also being considered. When an active energy ray-cured material is applied onto a film, generally, the film tends to warp or curl due to cure shrinkage, and this tendency becomes more pronounced as the film substrate becomes thinner. Since displays are constructed by laminating functional layers, curling of the substrate after the formation of the functional layers leads to poor workability in subsequent processes and reduced yields.
[0008] Patent Document 1 exemplifies a hard coat film having ultraviolet absorbing properties, which has both hard coat properties and ultraviolet absorbing properties.
[0009] However, if the transmittance (T)% at 380 nm is not set to an appropriate value, ultraviolet rays cannot be sufficiently blocked, and adverse effects on display products cannot be prevented. Also, if the transmittance (T)% at 380 nm is set to a sufficient value, when a benzotriazole or hydroxyphenyltriazine ultraviolet blocking agent is used, the transmittance decreases around 420 nm, causing the hue to take on a yellowish hue. Furthermore, if an attempt is made to make the product even thinner, the amount of UV blocking agent added will increase, making the yellowish hue even stronger. As a result, this has an adverse effect on the clarity of white light as a display product.
[0010] In addition, since an initiator that generates radicals when irradiated with ultraviolet light, including visible light, is used, the storage stability over time is poor and the coating process is easily affected by environmental factors such as lighting and temperature, leaving issues in terms of yield.
[0011] Patent Document 2 exemplifies a surface protection film that is less colored and has excellent scratch resistance by providing a resin layer containing a specific ultraviolet blocking agent on a base film.
[0012] However, as long as the ultraviolet ray blocking agent is selected from benzotriazole-based compounds and triazine-based compounds, the problem of yellowing due to a decrease in transmittance from around 420 nm, and the problem of increased yellowing due to an increase in the amount added when attempting to reduce the thickness, occur as in Patent Document 1, and have an adverse effect on the white clarity of the display product.
[0013] Furthermore, Patent Document 2 describes a UV initiator that has absorption up to around 390 nm. However, since the absorption wavelength end of the initiator and the cut wavelength region of the UV-blocking agent coincide or are close to each other, sufficient UV-curing properties cannot be obtained, resulting in reduced adhesion and reduced physical properties such as coating hardness, which causes problems. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2009-6513 A [Patent Document 2] JP 2016-107498 A Summary of the Invention [Problem to be solved by the invention]
[0015] The present invention provides an active energy ray-curable composition for forming a hard coat layer that protects a display part from external ultraviolet rays, improves white color clarity, prevents scratches during the production process, prevents curling due to cure shrinkage, and improves adhesion to a light-transmitting film, and provides a hard coat film and a laminate thereof using the same. [Means for solving the problem]
[0016] As a result of intensive research into the above-mentioned problems, the present inventors discovered that the problems could be solved by using the active energy ray-curable composition described below, and thus completed the present invention.
[0017] The present invention relates to an active energy ray-curable composition for forming a hard coat layer, which is a composition for forming a hard coat layer on a light-transmitting film, and which comprises an active energy ray-curable component (A), an ultraviolet ray cutter (B), a photopolymerization initiator (C), a color tone adjuster (D) and a solvent (E), wherein the active energy ray-curable component (A) comprises a polyfunctional urethane (meth)acrylate (a1) having six or more (meth)acryloyl groups and having a nurate ring skeleton, and the photopolymerization initiator (C) comprises an oxime ester derivative.
[0018] The present invention also relates to the active energy ray-curable composition for forming a hard coat layer, wherein the active energy ray-curable component (A) further contains a polyfunctional urethane (meth)acrylate (excluding (a1)) (a2) having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000, and another polyfunctional (meth)acrylate (a3).
[0019] The present invention also relates to a hard coat film having a hard coat layer formed on a light-transmitting film by curing the active energy ray-curable composition for forming a hard coat layer.
[0020] The present invention also relates to the hard coat film, which has a transmittance (ta) at a wavelength of 380 nm of 3% or less and a transmittance (tb) at a wavelength of 420 nm of 65% or more.
[0021] The present invention also provides L * a * b * In the color system, b * The hard coat film has a refractive index of -1.5 or more and 3.0 or less.
[0022] The present invention also provides L * a * b * In a * The hard coat film has a refractive index of -2.5 or more and 1.5 or less.
[0023] The present invention also relates to an optical laminate electronic device comprising the hard coat film and other functional layers laminated thereon. Effect of the Invention
[0024] The present invention can provide an active energy ray-curable composition for forming a hard coat layer that protects a display part from external ultraviolet rays, improves white color clarity, prevents scratches during the production process, prevents curling due to cure shrinkage, and improves adhesion to a light-transmitting film, as well as a hard coat film and a laminate thereof using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The present invention will be described in detail below. Needless to say, other embodiments are also included in the scope of the present invention as long as they are consistent with the gist of the present invention. In addition, in this specification, a numerical range specified using "~" includes the numerical values before and after "~" as the lower and upper limit ranges.
[0026] First, the terms used in this specification will be explained. In this specification, unless otherwise specified, the terms "(meth)acrylic", "(meth)acryloyl", and "(meth)acrylate" mean "acrylic or methacrylic", "acryloyl or methacryloyl", and "acrylate or methacrylate", respectively. In addition, "active energy ray curable composition for forming a hard coat layer" may be referred to as "composition for forming a hard coat layer", "urethane (meth)acrylate (a1) having 6 or more (meth)acryloyl groups and having a nurate ring skeleton" may be referred to as "urethane (meth)acrylate (a1)", and "multifunctional urethane (meth)acrylate (excluding (a1)) (a2) having 4 to 15 (meth)acryloyl groups and having a weight average molecular weight of 500 to 15,000" may be referred to as "multifunctional urethane (meth)acrylate (a2)". Unless otherwise noted, each of the various components appearing in this specification may be used independently, either alone or in combination of two or more.
[0027] <Active energy ray-curable component (A)> The active energy ray curable component (A) contains a polyfunctional urethane (meth)acrylate (a1) having 6 or more (meth)acryloyl groups and a nurate ring skeleton, and preferably further contains a polyfunctional urethane (meth)acrylate (excluding (a1)) (a2) having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000, and another polyfunctional (meth)acrylate (a3). The polyfunctional urethane (meth)acrylate refers to an oligomer having a urethane bond and two or more (meth)acrylate groups.
[0028] <Polyfunctional urethane (meth)acrylate (a1)> The urethane (meth)acrylate (a1) has six or more (meth)acryloyl groups and a nurate ring skeleton. The nurate ring skeleton is a trimer of an isocyanate compound having a nitrogen atom, and has a six-membered ring structure. By having six or more (meth)acryloyl groups, the crosslink density is increased, and the hard coat film surface has excellent hardness and scratch resistance, and the hard coat film can be prevented from curling. Although the detailed factors that prevent curling are unknown, it is believed that the ring structure of the nurate ring skeleton portion contributes greatly to stress relaxation. Compounds having three (meth)acryloyl groups and a nurate ring skeleton are relatively easy to obtain, but are not suitable because the hardness and scratch resistance of the hard coat film surface are insufficient due to their low crosslink density.
[0029] Specific examples of the urethane (meth)acrylate (a1) include a reaction product of an isocyanurate (trimer) of a diisocyanate with a poly(meth)acrylate compound having a hydroxyl group, and a reaction product of an isocyanurate (trimer) of a polyisocyanate with a polyol and a poly- or mono(meth)acrylate compound having a hydroxyl group. From the viewpoint of excellent hardness and scratch resistance of the hard coat film surface, a reaction product of an isocyanurate (trimer) compound of a diisocyanate with a poly(meth)acrylate compound having one hydroxyl group and two or more (meth)acryloyl groups is preferred.
[0030] Examples of diisocyanates include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate, hydrogenated products of the above aromatic isocyanates, and aliphatic diisocyanurates such as isophorone diisocyanate and hexamethylene diisocyanate. Examples of mono(meth)acrylates having one hydroxyl group include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate, and examples of poly(meth)acrylates having one hydroxyl group include, but are not limited to, pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.
[0031] The polyols include, but are not limited to, ethylene glycol, polyethylene glycol, polypropylene glycol, glycerin, trimethylolpropane, cyclohexanediol, cyclohexanedimethanol, and tricyclodecane dimethanol.
[0032] The content of the polyfunctional urethane (meth)acrylate (a1) in 100% by mass of the active energy ray-curable component (A) is preferably from 12 to 48% by mass. By adjusting the thickness within this range, curling can be suppressed.
[0033] <Polyfunctional urethane (meth)acrylate (a2)> The polyfunctional urethane (meth)acrylate (a2) is a polyfunctional urethane (meth)acrylate (excluding (a1)) having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000. The weight average molecular weight is preferably 1,000 to 5,000 in order to improve the hardness of the coating film after curing and maintain good curl properties. The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight determined by gel permeation chromatography (GPC) measurement. The weight average molecular weight can be measured by the method described in the [Examples] section.
[0034] The polyfunctional urethane (meth)acrylate (a2), when used in combination with the urethane (meth)acrylate (a1), can achieve a good balance between crosslink density, flexibility, and adhesion to the substrate, and can reduce the occurrence of scratches and curling (warping).
[0035] Examples of the polyfunctional urethane (meth)acrylate (a2) include those obtained by reacting a polyisocyanate with a mono(meth)acrylate or poly(meth)acrylate having a hydroxyl group, and those obtained by reacting an isocyanate group-containing urethane prepolymer obtained by reacting a polyol with a polyisocyanate under conditions of an excess of isocyanate groups with a mono(meth)acrylate or poly(meth)acrylate having a hydroxyl group. Alternatively, it can be obtained by reacting a hydroxyl group-containing urethane prepolymer obtained by reacting a polyol with a polyisocyanate under conditions of excess hydroxyl groups with a (meth)acrylate having an isocyanate group.
[0036] The following describes a method for producing the urethane (meth)acrylate (a2), but it is by way of example and is not intended to be limiting. For example, the urethane (meth)acrylate (a2) can be obtained by stirring a polyisocyanate and a hydroxyl group-containing (meth)acrylate in the presence of a suitable urethane-forming catalyst under an oxygen atmosphere at 60 to 100°C for 4 to 8 hours. Specific examples of urethanization catalysts include copper naphthenate, cobalt naphthenate, zinc naphthenate, dibutyltin dilaurate, triethylamine, 1,4-diazabicyclo[2.2.2]octane, 2,6,7-trimethyl-1,4-diazabicyclo[2.2.2]octane, etc. Among these, dibutyltin dilaurate is particularly preferred.
[0037] Examples of the polyisocyanate include aliphatic diisocyanates and aromatic diisocyanates, and examples of the aliphatic diisocyanates include hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate, and examples of the aromatic diisocyanates include toluene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate, and the bonding position of the isocyanate group with the aromatic group may be any of the ortho, meta, and para positions. The diisocyanate may also form an isocyanurate ring as a trimer. Among these, aliphatic diisocyanates are preferred from the viewpoint of suppressing yellowing when optical applications are envisaged.
[0038] The (meth)acryloyl number and weight average molecular weight can be adjusted by the combination of polyol, polyisocyanate, and hydroxyl group-containing mono(meth)acrylate or poly(meth)acrylate.
[0039] Examples of hydroxyl group-containing (meth)acrylates include trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, and Examples of the hydroxyl group-containing (meth)acrylic acid ester include 2-hydroxybutyl acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, ethyl-α-(hydroxymethyl) (meth)acrylate, monofunctional glycerol (meth)acrylate, or (meth)acrylic acid esters having a hydroxyl group at the end obtained by ring-opening addition of these (meth)acrylates to ε-caprolactone lactone, and alkylene oxide-added (meth)acrylic acid esters obtained by repeatedly adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to the above-mentioned hydroxyl group-containing (meth)acrylates. From the viewpoint of increasing the crosslink density and suppressing damage, curling, etc., a (meth)acrylic acid ester having 2 to 5 (meth)acrylolyl groups is preferred. Specifically, it is preferred to include at least one selected from trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.
[0040] Examples of urethane acrylates (a2) whose molecular weight and number of acryloyl groups are published in catalogs, etc., include Mitsubishi Chemical Corporation's Shiko UV1700B (molecular weight 2000, number of acryloyl groups 10), UV7600B (molecular weight 1400, number of acryloyl groups 6), UV7605B (molecular weight 1100, number of acryloyl groups 6), UV7610B (molecular weight 1100, number of acryloyl groups 9), and UV7629E. A (molecular weight 4100, number of acryloyl groups 9, volatile content 35%), UV7640B (molecular weight 1500, number of acryloyl groups 6-7), and UV7650B (molecular weight 2300, number of acryloyl groups 4-5); MIWON Co., Ltd.: Miramer PU610 (molecular weight 1800, number of acryloyl groups 6), and MU9500 (molecular weight 3200, number of acryloyl groups 10); Nippon Kayaku Co., Ltd.: KAYARAD DPHA-40H (molecular weight 2000, 10 acryloyl groups), UX-5000 (molecular weight 1500, 6 acryloyl groups), UX-5102D-M20 (molecular weight 3500, 6 acryloyl groups, 20% volatiles), UX-5103 (molecular weight 7000, 6 acryloyl groups), and UX-5005 (molecular weight 4500, 9 acryloyl groups), manufactured by Negami Chemical Industries, Ltd.: Art Resin UN-3320HA (molecular weight 1500, acryloyl groups) Examples of such acryloyl groups include, but are not limited to, UN-3320HC (molecular weight 1500, number of acryloyl groups 15, volatile content 5%), UN-904 (molecular weight 4900, number of acryloyl groups 10), UN-906S (molecular weight 1000, number of acryloyl groups 6), UN-901T (molecular weight 4000, number of acryloyl groups 9, volatile content 20%), and UN-952 (molecular weight 6500 to 11000, number of acryloyl groups 10).
[0041] The content of the polyfunctional urethane (meth)acrylate (a2) in 100% by mass of the active energy ray-curable component (A) is preferably from 20 to 80% by mass. By adjusting the thickness within this range, high scratch prevention can be achieved.
[0042] <Other polyfunctional (meth)acrylates (a3)> The other polyfunctional (meth)acrylate (a3) is a polyfunctional (meth)acrylate other than (a1) and (a2). Other examples of the polyfunctional (meth)acrylate (a3) include, but are not limited to, various diol (meth)acrylates, trimethylolethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, various polyol poly(meth)acrylates such as pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, tri(meth)acrylates of isocyanurates of various diisocyanates, and urethane acrylates other than the polyfunctional urethane acrylate (a1) and the polyfunctional urethane acrylate (a2). Pentaerythritol triacrylate (a3-1), pentaerythritol tetraacrylate (a3-2), dipentaerythritol pentaacrylate (a3-3), and dipentaerythritol hexaacrylate (a3-4), which remain during the synthesis of the urethane (meth)acrylate (a1) and the urethane (meth)acrylate (a2), can be used as they are.
[0043] Other examples of the polyfunctional (meth)acrylate (a3) include polyfunctional acrylates having 2 to 5 (meth)acryloyl groups and a nurate ring skeleton, such as isocyanuric acid EO-modified diacrylates (number of acryloyl groups: 2) such as ARONIX M-215 manufactured by Toagosei Co., Ltd., isocyanuric acid EO-modified diacrylates and / or triacrylates (number of acryloyl groups: 2 to 3) such as ARONIX M-313 manufactured by Toagosei Co., Ltd., and ARONIX M-315 manufactured by Toagosei Co., Ltd., ε-caprolactone-modified (2-acryloxy)isocyanurates (number of acryloyl groups: 3) such as NK ESTER A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., NK ESTER A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., SARTOMER SR368 manufactured by Arkema Co., Ltd., and NEW 1,2-dimethylaminoethyl acrylate manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Examples of the tris(2-acryloxyethyl)isocyanurate (number of acryloyl groups: 3) include, but are not limited to, FRONTIER TEICA (GX-8430) and Showa Denko's FANCRYL FA-731A.
[0044] Further, the other polyfunctional (meth)acrylate (a3) is a polyfunctional urethane acrylate having a (meth)acryloyl group number outside the range of 4 to 15 or a weight average molecular weight outside the range of 500 to 15,000. Examples of urethane acrylates include, but are not limited to, Shikoh UV-6300B (molecular weight 3700, number of acryloyl groups 3) manufactured by Mitsubishi Chemical Corporation, Art Resin UN-5500 (molecular weight 50000, number of acryloyl groups 12.5, volatile content 50%), UN-5507 (molecular weight 17000, number of acryloyl groups 15.5, volatile content 50%), and UN-905 (molecular weight 40000 to 200000, number of acryloyl groups 15, volatile content 40%) manufactured by Negami Chemical Industries Co., Ltd., and Miramer SC2152 (molecular weight 20787, number of acryloyl groups 15) manufactured by MIWON Co., Ltd.
[0045] The content of the other polyfunctional (meth)acrylate (a3) in 100% by mass of the active energy ray-curable component (A) is preferably 8 to 32% by mass. By adjusting the content within this range, high adhesion to the substrate can be achieved.
[0046] The mass ratio (a1) / (a2) of the polyfunctional urethane (meth)acrylate (a1) and the polyfunctional urethane (meth)acrylate (a2) contained in the active energy ray curable component (A) is preferably 20 / 80 to 80 / 20, more preferably 60 / 40 to 40 / 60. By setting the ratio (a1) / (a2) to 20 / 80 to 80 / 20, scratches during the process, adhesion to the substrate, and curling can be suppressed.
[0047] <UV protection agent (B)> The ultraviolet ray blocking agent (B) refers to an ultraviolet ray absorbing agent. By including (B), the composition for forming a hard coat layer of the present invention has ultraviolet ray absorbing properties. As the ultraviolet ray blocking agent (B), from the viewpoints of bleeding prevention, cost, etc., it is preferable to use one which has excellent ultraviolet ray absorbing ability even when added in a small amount. Examples of such ultraviolet ray blocking agents include benzotriazole-based, hydroxyphenyltriazine-based, and benzophenone-based ultraviolet ray blocking agents. Hydroxyphenyltriazine-based and benzotriazole-based UV-blocking agents are preferred from the viewpoint of minimizing adverse effects on other physical properties of the coating film. The UV-blocking agent may be a commercially available product as is, or two or more types of commercially available products may be mixed and used.
[0048] Examples of commercially available ultraviolet ray blocking agents include the "TINUVIN" series (benzotriazole-based and hydroxyphenyltriazine-based) and "CHIMASSORB" series manufactured by Ciba Specialty Chemicals, Inc., the "UVINUL" series (benzophenone-based and triazine-based) manufactured by BASF Ltd., the "RUVA" series (benzotriazole-based) manufactured by Otsuka Chemical Co., Ltd., the "ADEGASTABE LA" series (benzotriazole-based and triazine-based) manufactured by ADEKA Corp., and the "Eversorb" series (benzotriazole-based, triazine-based, benzophenone-based) manufactured by Ever Light Chemicals.
[0049] The content of the ultraviolet ray blocking agent (B) is, for example, 0.5 to 20 mass%, preferably 2 to 15 mass%, relative to 100 mass% of the active energy ray curable component (A). By setting the content to 0.5 to 20 mass%, ultraviolet rays necessary for photoexciting the photopolymerization initiator can be secured while sufficient ultraviolet rays are blocked, and the curability of the coating film can be improved.
[0050] <Photopolymerization initiator (C)> The photopolymerization initiator (C) includes an oxime ester derivative. The active energy ray curable composition of the present invention contains an ultraviolet ray cutter, and thus cuts ultraviolet rays having a wavelength of approximately less than 400 nm, which is close to visible light and affects laminates, and therefore cuts ultraviolet rays necessary for photoexcitation of many photopolymerization initiators, such as 313 nm (j-ray) and 365 nm (i-ray), emitted from mercury-containing ultraviolet lamps, such as high-pressure mercury lamps and metal halide lamps, which are generally used for ultraviolet curing. However, by using an oxime ester derivative, radical polymerization can be initiated by photoexcitation with ultraviolet rays of 400 nm or more (for example, 405 nm h-ray, etc.).
[0051] Examples of conventionally known oxime ester derivatives include Irgacure OXE01, Irgacure OXE02, Irgacure OXE03, Irgacure OXE04, etc., manufactured by BASF Ltd., Nikkacure YJ-04, IW-15, etc., manufactured by Nippon Chemical Industry Co., Ltd., and Adeka Arcles NCI-831E, manufactured by ADEKA Corporation.
[0052] The photopolymerization initiator (C) may be used in combination with other photopolymerization initiators other than the oxime ester derivatives. Examples of other photopolymerization initiators include acetophenone compounds, benzoin compounds, benzophenone compounds, phosphine oxide compounds, ketal compounds, anthraquinone compounds, and thioxanthone compounds. Specific examples include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, diethoxyacetophenone, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, benzophenone, 2,4,6-trimethylbenzoin diphenylphosphine oxide, N,N-dimethylaminobenzoic acid isoamyl, 2-chlorothioxanthone, and 2,4-diethylthioxanthone.
[0053] The initiator to be used in combination is preferably a highly sensitive initiator capable of efficiently generating radicals even with as little UV light as possible.Specific examples include dialkylaminobenzophenone derivatives such as 4,4'-bis(dimethylamino)benzophenone and 4,4'-bis(diethylamino)benzophenone, camphorquinone derivatives such as (±)-camphorquinone, Ultracure CTX and Ultra cure DTX manufactured by Sherwin-Williams, Quantacure ITX manufactured by Ward-Blenkinsop, thioxanthone derivatives such as isopropylthioxanthone and 2,4-diethylthioxanthone, and anthraquinone derivatives such as TBA and 2-ethylanthraquinone manufactured by BASF.
[0054] The amount of the photopolymerization initiator (C) is preferably 0.1 to 30% by mass, more preferably 1 to 15% by mass, based on 100% by mass of the total of the active energy ray-curable components (A). Within this range, a sufficient polymerization initiation effect is obtained, which is effective in improving adhesion and scratch resistance.
[0055] <Color tone adjuster (D)> The color tone adjusting agent in the present invention is an additive that adjusts the color tone by absorbing light in the visible light region. The type of the color tone adjusting agent is not particularly limited, but in order to adjust the yellowish color of the hard coat layer, a known dye or pigment can be used as a colorant that exhibits blue or purple.
[0056] In addition, the blue color adjuster used to adjust the yellow color gives the product a greenish color (a * If the concentration of the compound changes to the negative side, add a red or purple color adjuster to adjust the concentration of the compound. * a * b * By adjusting the coordinates to the center of the color system, * This can improve white clarity even more than color adjustment by adjusting the brightness. Known dyes and pigments can be used as color tone adjusters that provide red or purple color.
[0057] Examples of dyes include organic dyes such as monoazo dyes having an azo group in the molecule, triarylmethane dyes, phthalocyanine dyes, and anthraquinone dyes, and inorganic dyes such as iron blue, Prussian blue, Berlin blue, Turnbull blue, Milory blue, Chinese blue, and Paris blue (iron cyano complex colorants); ultramarine blue, ultramarine violet, and other ultramarine blues; and cobalt blue. Examples of the pigment include blue pigments such as CI Pigment Blue 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, 22, 60, and 80. Of these, it is preferable to use a blue pigment selected from the group consisting of CI Pigment Blue 15:6. As the purple pigment, CI Pigment Violet 19 or CI Pigment Violet 23 is preferred. Examples of red pigments include CI Pigment Red 7, 9, 14, 41, 48:2, 48:3, 48:4, 81:1, 81:2, 81:3, 97, 122, 123, 146, 149, 168, 178, 180, 184, 185, 187, 192, 200, 202, 208, 210, 215, 216, 217, 220, 223, 224, 226, 227, 228, 240, 246, 255, 264, and 272. Of these, it is preferable to use a red pigment selected from the group consisting of CI Pigment Red 48:1, 177, 242, and 254.
[0058] From the viewpoint of heat resistance, light resistance, and weather resistance, the use of pigments is preferred, as the use of pigments provides heat resistance, light resistance, and weather resistance suitable for outdoor use. The color tone adjusting agents can be used alone or in combination of two or more.
[0059] The content of the color tone adjusting agent may be appropriately adjusted so that the hard coat film having a hard coat layer of a predetermined thickness has a desired transmittance. For example, when the transmittance (ta) at 380 nm of the hard coat film having a hard coat layer of a thickness of 5 μm is to be 3% or less, the content of the color tone adjusting agent is preferably 0.001 to 4.0% by mass, more preferably 0.01 to 2.5% by mass, based on 100% by mass of the active energy ray curable component (A) in terms of suppression of yellowing and transparency.
[0060] When a pigment is used as a color tone adjuster, the volume average primary particle size of the pigment is preferably 150 nm or less from the viewpoint of transparency of the hard coat layer, and the average dispersed particle size (D50) of the pigment in the composition is preferably 10 to 150 nm.
[0061] The volume average primary particle diameter of a pigment is determined by measuring the short and long axis diameters of 100 primary particles of the pigment using transmission electron microscope (TEM) photographs, taking the average of the short and long axis diameters as the particle diameter (d) of the pigment particle, and then determining the volume (V) of each particle by assuming that each pigment is a sphere having the determined particle diameter. This procedure is performed for 100 pigment particles, and the volume average particle diameter (MV) obtained from the following formula is used as the average primary particle diameter. MV = Σ(V d) / Σ(V) The average dispersed particle size (D50) of the pigment in the composition can be measured by a particle size distribution measuring device, particularly a particle size distribution measuring device using dynamic light scattering (such as Microtrack Bell's "NANOTRAC WAVE II EX150").
[0062] To obtain a pigment having a volume average primary particle size of 150 nm or less, the particles can be finely divided by, for example, salt milling. In order to obtain an average dispersed particle size (D50) of 10 to 150 nm in the active energy ray-curable composition, it is preferable to disperse the pigment, and it is preferable to use a pigment dispersion in which the pigment has been dispersed in advance.
[0063] A pigment dispersion in which a pigment is dispersed can be produced by finely dispersing a mixture of a pigment, a dispersant, and / or a binder resin, and an organic solvent using various dispersing means such as a kneader, a two-roll mill, a three-roll mill, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, or an attritor (pigment dispersion). In particular, it is preferable to carry out bead dispersion using zirconium oxide or inorganic glass, and beads of different diameters may be used in this case.
[0064] When dispersing the pigment, a dispersant such as a dye derivative, a resin-type dispersant, a surfactant, etc. may be appropriately added. Fine pigments tend to reaggregate and may reduce the transparency of the coating film, but dispersants have a large effect of preventing the reaggregation of pigments, and therefore the transparency of the coating film is improved.
[0065] The dye derivatives include those having a basic substituent or an acidic substituent in the dye skeleton. For example, those described in JP-A-63-305173, JP-B-57-15620, JP-B-59-40172, JP-B-63-17102, or JP-B-5-9469 can be used, and these can be used alone or in combination of two or more kinds.
[0066] Resin-type pigment dispersants have a pigment-affinity site that has the property of being adsorbed to the pigment and a site that is compatible with the pigment carrier, and act to stabilize the dispersion of the pigment in the pigment carrier by adsorbing to the pigment.Specific examples of resin-type pigment dispersants include polyurethane, polyacrylate and other polycarboxylate esters, unsaturated polyamides, polycarboxylic acids, polycarboxylate (partial) amine salts, polycarboxylate ammonium salts, polycarboxylate alkylamine salts, polysiloxanes, long-chain polyaminoamide phosphate salts, hydroxyl-containing polycarboxylate esters, and their modifications, oil-based dispersants such as amides formed by the reaction of poly(lower alkylene imine) with polyesters having free carboxyl groups and their salts, water-soluble resins and water-soluble polymer compounds such as (meth)acrylic acid-styrene copolymers, (meth)acrylic acid-meth)acrylic acid ester copolymers, styrene-maleic acid copolymers, polyvinyl alcohol, and polyvinylpyrrolidone, polyesters, modified polyacrylates, ethylene oxide / propylene oxide adducts, and phosphate esters, which can be used alone or in combination of two or more.
[0067] Commercially available resin-type dispersants include DISPERBYK-101, 103, 107, 108, 109, 110, 111, 116, 130, 140, 154, 161, 162, 163, 164, 165, 166, 167, 168, 170, 171, 174, 180, 181, 182, 183, 184, 185, 190, 2000, 2001, 2020, 2025, 2050, 2070, 2095, 2150, 2155, 2163, 2164, or Anti-Terra-U, 203, 204, or BYK-P104, P104S, 220S, 6919, or Lactimon, Lactimon-WS, or Bykumen, SOLSPERSE-3000, 9000, 11200, 13000, 13240, 13650, 13940, 16000, 17000, 18000, 20000, 21000, 24000, 26000, 27000, 280 made by Louvre Resol Japan 00, 31845, 32000, 32500, 32550, 33000, 33500, 32600, 34750, 35100, 35200, 36600, 37500, 38500, 39000, 41000, 41090, 53090, 56000, 55000, 71000, 76500, etc., EFKA-46, 47, 48, 452, 4008, 4009, 4010, 4015, 4020, 4047, 4050, 4055, 4060, 4080 manufactured by BASF , 4400, 4401, 4402, 4403, 4406, 4408, 4300, 4310, 4320, 4330, 4340, 4500, 4510, 4530, 4540, 4550, 4560, 4800, 5010, 5065, 5066, 5070, 7500, 7554, 1101, 120, 150, 1501, 1502, 1503, etc., and Ajisper PA111, PB711, PB821, PB822, PB824, etc. manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0068] Examples of the surfactant include anionic surfactants such as polyoxyethylene alkyl ether sulfate, sodium dodecylbenzene sulfonate, alkali salts of styrene-acrylic acid copolymers, sodium alkyl naphthalene sulfonate, sodium alkyl diphenyl ether disulfonate, monoethanolamine lauryl sulfate, triethanolamine lauryl sulfate, ammonium lauryl sulfate, monoethanolamine stearate, sodium stearate, sodium lauryl sulfate, monoethanolamine of styrene-acrylic acid copolymers, and polyoxyethylene alkyl ether phosphates; nonionic surfactants such as polyoxyethylene oleyl ether, polyoxyethylene lauryl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl ether phosphates, polyoxyethylene sorbitan monostearate, and polyethylene glycol monolaurate; cationic surfactants such as alkyl quaternary ammonium salts and their ethylene oxide adducts; and amphoteric surfactants such as alkyl betaines such as alkyl dimethylaminoacetate betaine and alkyl imidazolines, which may be used alone or in combination of two or more.
[0069] When a dispersant is added, the amount is preferably 0.1 to 200 parts by mass, and more preferably 0.1 to 150 parts by mass, per 100 parts by mass of the pigment. If the amount of the dispersant is less than 0.1 parts by mass, it is difficult to obtain the desired effect, whereas if the amount is more than 200 parts by mass, the excess dispersant may adversely affect dispersion.
[0070] The binder resin is not particularly limited as long as it can form a thin film layer and can disperse a pigment. Examples of the binder resin include known thermoplastic resins, energy ray curable resins such as UV curable resins, and thermosetting resins. Examples of the UV curable resin include resins having a polymerizable functional group such as a (meth)acryloyl group. These resin components can be used alone or in combination of two or more. Among these, energy ray curable resins such as UV curable resins are preferred as the resin component because they increase the curability of the final composition coating film and improve physical properties such as coating film hardness and adhesion.
[0071] <Solvent (E)> Examples of the solvent (E) include, but are not limited to, dimethyl carbonate, ethyl acetate, n-butyl acetate, acetone, methyl ethyl ketone, cyclohexanone, 1,3-dioxolane, methyl isobutyl ketone, isopropyl alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, toluene, etc. Also, one type may be used alone or two or more types may be used in combination.
[0072] The content of the solvent (E) is preferably 40 to 80 mass %, more preferably 40 to 70 mass %, and further preferably 45 to 65 mass %, in 100 mass % of the active energy ray-curable composition for forming a hard coat layer. When the content is within the above range, the viscosity of the active energy ray-curable composition for forming a hard coat layer can be reduced and the coatability and drying property can be adjusted.
[0073] <<Active energy ray-curable composition for forming hard coat layer>> The active energy ray-curable composition for forming a hard coat layer of the present invention contains an active energy ray-curable component (A), an ultraviolet ray blocking agent (B), a photopolymerization initiator (C), a hue adjuster (D) and a solvent (E).
[0074] The composition for forming a hard coat layer in the present invention may contain other additives as necessary, such as a plasticizer, a surface conditioner, a light stabilizer, an antioxidant, and a polymerization inhibitor.
[0075] <Hard coat film> The hard coat film of the present invention has a hard coat layer formed by curing the above-mentioned composition for forming a hard coat layer on a light-transmitting film. The hard coat film of the present invention preferably has a transmittance (ta) of 3% or less at a wavelength of 380 nm and a transmittance (tb) of 65% or more at a wavelength of 420 nm. By having a transmittance (ta) of 3% or less at a wavelength of 380 nm, ultraviolet light having a wavelength of 380 nm or less that is harmful to displays is cut, making it possible to prevent deterioration of the display area. Furthermore, since the transmittance (tb) at a wavelength of 420 nm is 65% or more, it is possible to improve the clarity of white in the display area. The transmittance (ta) is more preferably 1.5% or less, and the transmittance (tb) is more preferably 70% or more from the viewpoint of suppressing yellowing.
[0076] The hard coat film of the present invention is excellent in terms of white clarity of the display area. * a * b * In the color system, b * is preferably -1.5 or more and 3.0 or less. * is preferably not less than −2.5 and not more than 1.5.
[0077] (Light-transmitting film) The light-transmitting film used in the present invention may be of an optically transparent grade, and the thickness of the film is not particularly limited, but is generally about 10 to 500 μm in terms of strength, workability such as handling, thinness, etc. In particular, 20 to 250 μm is preferred.
[0078] Specific examples of light-transmitting films include amorphous polyolefin resin films, polyester resin films, polyethylene terephthalate resin films, acrylic resin films, polycarbonate resin films, polysulfone resin films, alicyclic polyimide resin films, polycycloolefin resin films, triacetyl cellulose (TAC) films, etc. An optimal film may be used depending on the display structure, and there are no limitations as long as it is optically transparent.
[0079] (Hard coat film manufacturing) The method for producing the hard coat film is not particularly limited, and the hard coat film can be produced by a conventionally known method, such as coating a composition for forming a hard coat layer on a light-transmitting film. For example, the composition for forming a hard coat layer of the present invention is applied to a light-transmitting film, and then the solvent is dried as necessary. The applied composition for forming a hard coat layer is crosslinked and cured by irradiating the composition with active energy rays, thereby forming a light-transmitting film. Thus, a hard coat film having a hard coat layer and a hard coat film having a hard coat layer can be obtained.
[0080] Examples of the coating method include bar coating, blade coating, spin coating, reverse coating, die coating, spray coating, roll coating, gravure coating, microgravure coating, lip coating, air knife coating, and dipping.
[0081] Examples of active energy rays that can be used include electron beams and ultraviolet rays emitted from light sources such as xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, extra-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps. The active energy ray-curable composition of the present invention contains an ultraviolet ray blocking agent, thereby blocking ultraviolet rays with a wavelength of about 400 nm, which is close to visible light. Therefore, it is preferable to use a high-pressure mercury lamp or a metal halide lamp having an emission spectrum with a wavelength of 400 nm or more.
[0082] The thickness of the hard coat layer is not particularly limited as long as it has hard coat properties, and is usually 1 to 20 μm, and preferably 1 to 15 μm.
[0083] <<Optical laminated electronic device>> The optical laminated electronic device of the present invention is formed by laminating a hard coat film and other functional layers, for example, a laminate of a hard coat film and a display functional layer, and has a structure of hard coat layer / optical film / display functional layer. The method for producing the laminate is not particularly limited, but for example, a display functional layer laminate that is protected from harmful ultraviolet rays from the outside can be formed by adhering a light-transmitting film surface that does not have a hard coat layer of a hard coat film to a display functional layer. EXAMPLES
[0084] <Weight average molecular weight (Mw)> The weight average molecular weight is the polystyrene equivalent weight average molecular weight measured at a flow rate of 0.6 ml / min using a gel permeation chromatography "HLC-8220GPC" manufactured by Tosoh Corporation, with four separation columns "TSK-GEL SUPER H5000," "TSK-GEL SUPER H4000," "TSK-GELSUPER H3000," and "TSK-GEL SUPER H2000" manufactured by Tosoh Corporation connected in series, and using tetrahydrofuran at a temperature of 40°C as the mobile phase.
[0085] <Average dispersed particle diameter (D50)> The average dispersed particle diameter (D50) was measured using a dynamic light scattering particle size distribution analyzer (Microtrack-Bell Corporation, "NANOTRAC WAVE II EX150"). Propylene glycol monomethyl ether acetate was used as the dilution solvent, and the average value of three 60-second measurements was used at a concentration where the loading index was in the range of 1.0±0.2.
[0086] <Production of polyfunctional urethane acrylate (a1)> (Synthesis Example 1) Urethane acrylate mixed solution (P1): Into a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, 1,325.6 parts by mass of ARONIX M306 (manufactured by Toagosei Co., Ltd., a pentaerythritol polyacrylate containing 67.5% by mass of pentaerythritol triacrylate (PE-3A) (a3-1) having a molecular weight of 298 and 32.5% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2) having a molecular weight of 352) was added. 0.1 parts by mass of Neostan U-810 (manufactured by Nitto Kasei Co., Ltd., tin catalyst) was added and the liquid temperature was raised to 50°C, after which 1,059.3 parts by mass of Desmodur Z4470BA (manufactured by Sumika Covestro Co., Ltd., non-volatile content 70% by mass (volatile content butyl acetate), containing 89.9% by mass of isophorone diisocyanate (IPDI) trimer having a molecular weight of 667 relative to the non-volatile content, and having a nurate ring with an NCO content of 11.9%) was added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the isocyanate group peak had disappeared by Fourier transform infrared spectroscopy (FT-IR), the temperature was lowered to room temperature, and a urethane acrylate mixture (P1) was obtained with a non-volatile content of 86.7% by mass, containing 75.5% by mass of urethane acrylate (a1-1) having 9 acryloyl groups and a weight average molecular weight of 1600, 20.8% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2), and 3.6% by mass of other compounds (f-1) having no (meth)acryloyl groups.
[0087] Synthesis Example 2 Urethane acrylate mixed liquid (P2): 1,325.6 parts by mass of Aronix M306 and 0.1 parts by mass of Neostan U-810 were placed in a four-necked flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, and the liquid temperature was adjusted to 50°C. After that, 545.7 parts by mass of Duranate TPA-100 (manufactured by Asahi Kasei Corporation, 100% by mass nonvolatile content, containing 92.8% by mass of hexamethylene diisocyanate (HDI) trimer having a molecular weight of 505 relative to the nonvolatile content, and having a nurate ring with an NCO content of 23.1%) was added dropwise from the dropping funnel over 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After it was confirmed that the isocyanate group peak had disappeared in FT-IR, the temperature was lowered to room temperature, and a urethane acrylate mixture (P2) with a non-volatile content of 100% by mass was obtained, containing 74.8% by mass of urethane acrylate (a1-2) having 9 acryloyl groups and a weight average molecular weight of 1,400, 23.0% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2), and 2.2% by mass of other compounds (f-2) having no (meth)acryloyl groups.
[0088] Synthesis Example 3 Urethane acrylate mixed solution (P3): 4237.3 parts by mass of Desmodur Z4470BA, 432.6 parts by mass of cyclohexyldimethanol (molecular weight 144, hydroxyl value 389 mgKOH / g), and 0.1 part by mass of Neostan U-810 were placed in a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, and the mixture was heated to 80° C. The temperature was raised to 80°C and reacted for 3 hours. After it was confirmed that the peak intensity of the isocyanate group in FT-IR was 50% of that before the reaction, 865.0 parts by mass of 4-hydroxybutyl acrylate (molecular weight 144, hydroxyl value 389 mgKOH / g) was added, and the mixture was reacted at 80°C for a further 3 hours. After it was confirmed that the peak of the isocyanate group in FT-IR had disappeared, the temperature was lowered to room temperature, and a urethane acrylate mixed liquid (P3) with a non-volatile content of 100.0% by mass was obtained, which contained, in the non-volatile content, 93.0% by mass of urethane acrylate (a1-3) having 6 acryloyl groups and a weight average molecular weight of 4000, and 7.0% by mass of other compound (f-3) having no (meth)acryloyl group.
[0089] (Synthesis Example 4) Urethane acrylate mixed liquid (P4): 894.8 parts by mass of Pentaerythritol Triacrylate (manufactured by Thermo Fisher Scientific, pentaerythritol triacrylate (PE-3A), purity 97% or more, molecular weight 298) and 0.1 parts by mass of Neostan U-810 (manufactured by Nitto Kasei Co., Ltd., tin catalyst) were placed in a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, and the liquid temperature was increased to 50°C. After that, 1059.33 parts by mass of Desmodur Z4470BA (manufactured by Sumika Covestro Co., Ltd., non-volatile content 70% by mass (volatile content butyl acetate), non-volatile content containing 89.9% by mass of isophorone diisocyanate (IPDI) trimer having a molecular weight of 667 relative to the non-volatile content, and having a nurate ring with an NCO content of 11.9%) was dropped from the dropping funnel over 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the isocyanate group peak had disappeared by Fourier transform infrared spectroscopy (FT-IR), the temperature was lowered to room temperature, and a urethane acrylate mixture (P4) was obtained with a non-volatile content of 83.7% by mass, containing 95.4% by mass of urethane acrylate (a1-1) having 9 acryloyl groups and a weight average molecular weight of 1600, and 4.6% by mass of other compound (f-1) having no (meth)acryloyl groups.
[0090] <Production of urethane acrylate (a2) having 4 to 15 (meth)acryloyl groups and a molecular weight of 500 to 15,000> (Synthesis Example 5) Urethane acrylate mixed solution (Q1): 533 parts by mass of Pentaerythritol Triacrylate (manufactured by Thermo Fisher Scientific, pentaerythritol triacrylate (PE-3A), purity 97% or more, molecular weight 298), 237 parts by mass of ARONIX M306, and 100.1 parts by mass of Neostan U-8 were placed in a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, and the liquid temperature was raised to 50°C. Then, 224 parts by mass of Desmodur I (manufactured by Sumika Covestro Co., Ltd., isophorone diisocyanate (IPDI)) was added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After it was confirmed that the isocyanate group peak had disappeared in FT-IR, the temperature was lowered to room temperature, and a urethane acrylate mixture (Q1) was obtained, which contained, in the non-volatile matter, 82.4 mass% of urethane acrylate (a2-1) having a molecular weight of 900 and 6 acryloyl groups, 9.7 mass% of pentaerythritol triacrylate (a3-1) (PE-3A, acryloyl group equivalent of 99), and 7.8 mass% of pentaerythritol tetraacrylate (a3-2) (PE-4A).
[0091] (Synthesis Example 6) Urethane acrylate mixed solution (Q2): A four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel was charged with 2500 parts by mass of ARONIX M403 (manufactured by Toagosei Co., Ltd., a mixture of 55% by mass of dipentaerythritol pentaacrylate (DPPA (a3-3)) having a molecular weight of 524 and 45% by mass of dipentaerythritol hexaacrylate (DPHA (a3-4)) having a molecular weight of 579) and 0.1 parts by mass of Neostan U-810, and the liquid temperature was raised to 50°C. After that, 224 parts by mass of Desmodur I was dropped from the dropping funnel over 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After it was confirmed that the isocyanate group peak had disappeared in FT-IR, the temperature was lowered to room temperature, and a urethane acrylate mixture (Q2) was obtained, which contained, in the non-volatile matter, 46.7 mass% of urethane acrylate (a2-2) having a molecular weight of 1,300 and 10 acryloyl groups, 12.0 mass% of dipentaerythritol pentaacrylate (a3-3) (DPPA, acryloyl group equivalent of 105), and 41.3 mass% of dipentaerythritol hexaacrylate (a3-4) (DPHA).
[0092] The materials used in the examples and comparative examples are described below.
[0093] <Polyfunctional urethane (meth)acrylate (a1)> (a1-1): molecular weight 1600, number of acryloyl groups 9 (a1-2): molecular weight 1400, number of acryloyl groups 9 (a1-3): molecular weight 4000, number of acryloyl groups 6 <Polyfunctional urethane (meth)acrylate (a2)> (a2-1): molecular weight 900, number of acryloyl groups 6 (a2-2): molecular weight 1300, 10 acryloyl groups <Polyfunctional (meth)acrylate (a3)> (a3-1): Pentaerythritol triacrylate (PE-3A) (a3-2): Pentaerythritol tetraacrylate (PE-4A) (a3-3): Dipentaerythritol pentaacrylate (DPPA) (a3-4): Dipentaerythritol hexaacrylate (DPHA) Multifunctional acrylate liquid (R1): Aronix M-403 (a mixture of 55% dipentaerythritol pentaacrylate (a3-3) and 45% dipentaerythritol hexaacrylate (a3-4) manufactured by Toagosei Co., Ltd. Multifunctional acrylate liquid (R2): SARTOMER SR368 (molecular weight 423, number of acryloyl groups 3, (a3-5)) manufactured by Arkema Co., Ltd. Multifunctional acrylate liquid (R3): Negami Chemical Industries Co., Ltd.: Art Resin UN-5507 (molecular weight 17000, number of acryloyl groups 15.5, (a3-6), contains 50% PGMAC (propylene glycol monomethyl ether acetate))
[0094] <Preparation of blue pigment for dispersion> 100 parts of blue pigment CI Pigment Blue 15:6 ("Lionol Blue ES" manufactured by Toyo Color Co., Ltd.), 800 parts of ground salt, and 100 parts of diethylene glycol were charged into a stainless steel 1-gallon kneader (manufactured by Inoue Seisakusho Co., Ltd.) and kneaded at 70°C for 12 hours. This mixture was added to 3000 parts of warm water, heated to about 70°C and stirred with a high-speed mixer for about 1 hour to form a slurry, which was filtered and washed repeatedly to remove salt and solvent, and then dried at 80°C for 24 hours to obtain 98 parts of blue fine pigment (BP). The volume average primary particle diameter of the resulting pigment was 28.3 nm.
[0095] <Preparation of blue pigment dispersion (dB)> The mixture below was stirred and mixed until homogeneous, then dispersed for 5 hours in an Eiger mill (Eiger Japan's "Mini Model M-250MKII") using zirconia beads with a diameter of 0.5 mm, and then filtered through a 5.0 μm filter to obtain a pigment dispersion. The pigment dispersion was adjusted with PGMAc (propylene glycol monomethyl ether acetate) to a non-volatile content of 20 mass%, and dB was obtained. Blue fine pigment (BP): 11.1 parts by weight Dispersant (Ajisper PB821, manufactured by Ajinomoto Fine Techno, DS): 12.1 parts by weight Propylene glycol monomethyl ether acetate: 76.8 parts by weight The average dispersed particle size (D50) of the resulting dispersion was 55 nm.
[0096] <Preparation of purple pigment for dispersion> 100 parts of purple pigment CI Pigment Violet 23 ("LIONOGEN VIOLET FG-6140" manufactured by Toyo Color Co., Ltd.), 800 parts of ground salt, and 100 parts of diethylene glycol were charged into a stainless steel 1-gallon kneader (manufactured by Inoue Seisakusho Co., Ltd.) and kneaded at 70°C for 12 hours. This mixture was added to 3000 parts of warm water, heated to about 70°C and stirred with a high-speed mixer for about 1 hour to form a slurry, filtered and washed repeatedly with water to remove salt and solvent, and then dried at 80°C for 24 hours to obtain 95 parts of a purple fine pigment (VP). The volume average primary particle diameter of the obtained pigment was 53.7 nm.
[0097] <Preparation of purple dispersion (dV)> The mixture below was stirred and mixed until homogeneous, then dispersed in an Eiger mill (Eiger Japan's "Mini Model M-250 MKII") using zirconia beads with a diameter of 0.5 mm for 3 hours, and then filtered through a filter with a pore size of 5.0 μm to obtain a pigment dispersion. The pigment dispersion was adjusted with PGMAc (propylene glycol monomethyl ether acetate) to a non-volatile content of 20 mass % to produce a violet dispersion (dV). Purple micronized pigment (VP): 14.0 parts Dispersant (Ajisper PB821, manufactured by Ajinomoto Fine Techno, DS): 10.1 parts by weight Propylene glycol monomethyl ether acetate (PGMAc) :75.9 copies The average dispersed particle size (D50) of the resulting dispersion was 100 nm.
[0098] <Preparation of red pigment for dispersion> 200 parts of CI Pigment Red 254 (BASF "S3610CF"), 1400 parts of sodium chloride, and 360 parts of diethylene glycol were charged into a stainless steel 1-gallon kneader (Inoue Seisakusho) and kneaded at 80°C for 6 hours. Next, this kneaded mixture was added to 8000 parts of warm water, heated to 80°C and stirred for 2 hours to form a slurry, filtered and washed with water repeatedly to remove sodium chloride and diethylene glycol, and then dried at 85°C for a day and night to obtain 190 parts of red fine pigment (RP). The volume average primary particle diameter was 27.6 nm.
[0099] <Preparation of red pigment dispersion (dR)> The mixture below was stirred and mixed until homogeneous, then dispersed in an Eiger mill (Mini Model M-250MKII, manufactured by Eiger Japan) using zirconia beads with a diameter of 0.5 mm for 5 hours, and then filtered through a 5.0 μm filter to obtain a pigment dispersion. The pigment dispersion was adjusted with PGMAc (propylene glycol monomethyl ether acetate) to a non-volatile content of 20 mass % to produce a red pigment dispersion (dR). Red fine pigment (RP): 14.4 parts Dispersant (Ajisper PB821, manufactured by Ajinomoto Fine Techno, DS): 10.1 parts Propylene glycol monomethyl ether acetate: 75.5 parts The average dispersed particle diameter (D50) of the resulting dispersion was 50 nm.
[0100] <UV protection agent (B)> UV protection agent (b-1): BASF: UVINUL 3050: Benzophenone-based UV protection agent
[0101] <Photopolymerization initiator (C)> (c-1): BASF: Irgacure OXE03: Oxime ester derivative (c-2): BASF: Irgacure OXE01: Oxime ester derivative (c-3): IGM Resins BV: ESACURE ONE: Oligo[2-hydroxy-2-methyl-[1-(methylvinyl)phenyl]propanone
[0102] <Solvent (E)> (e-1): Butyl acetate (manufactured by Sankyo Chemical Co., Ltd.) (e-2): MEK (methyl ethyl ketone, manufactured by Taishin Chemical Co., Ltd.) (e-3): PGM (propylene glycol monomethyl ether, manufactured by Taishin Chemical Co., Ltd.) (e-4): PGMAC (propylene glycol monomethyl ether acetate, manufactured by Sankyo Chemical Co., Ltd.) (e-5): DMC (dimethyl carbonate, manufactured by UBE Corporation) (e-6): MIBK (Methyl isobutyl ketone, manufactured by Mitsubishi Chemical Corporation)
[0103] <Example 1> Into a flask equipped with a stirrer, 21.4 parts of urethane acrylate liquid (P1), 67.9 parts of urethane acrylate liquid (Q1), 14.2 parts of multifunctional acrylate liquid (R1), 10.0 parts of ultraviolet ray cutter UVINUL3050 (b-1), 10.0 parts of photopolymerization initiator Irugacure OXE03 (c-1), 76.7 parts of methyl ethyl ketone (e-2), 20.0 parts of propylene glycol monomethyl ether (e-3), 0.176 parts of blue pigment dispersion (dB) and 0.418 parts of purple pigment dispersion (dV) as color tone adjusters were added, and the mixture was stirred and mixed to obtain a hard coat layer forming composition containing the following compounds. Urethane acrylate (a1-1): 14.0 parts Urethane acrylate (a2-1): 56.0 parts Pentaerythritol triacrylate (a3-1): 6.6 parts Pentaerythritol tetraacrylate (a3-2): 9.2 parts Dipentaerythritol pentaacrylate (a3-3): 7.8 parts Dipentaerythritol hexaacrylate (a3-4): 6.4 parts Total of active energy ray curing component (A) 100.0 parts Other non-volatile matter (f-1): 0.6 parts UV protection agent UVINUL3050(b-1): 10.0 parts Photopolymerization initiator Irgacure OXE03(c-1): 10.0 parts Blue micropigment (BP): 0.017 parts Purple micronized pigment (VP): 0.049 parts Dispersant (DS): 0.053 parts n-Butyl acetate (e-1): 2.8 parts Methyl ethyl ketone (MEK) (e-2): 76.7 parts Propylene glycol monomethyl ether (PGM) (e-3): 20.0 parts Propylene glycol monomethyl ether acetate (PGMAC) (e-4): 0.475 parts
[0104] <Examples 2 to 29 and Comparative Examples 1 to 7> As shown in Tables 1 to 3, compositions for forming a hard coat layer of Examples 2 to 29 and Comparative Examples 1 to 7 were produced in the same manner as in Example 1, except that the compositions and blending amounts (parts by mass) were changed.
[0105] The obtained composition for forming a hard coat layer was used to measure the transmittance, a * , b * The results are shown in Tables 1 to 3.
[0106] [Transmittance measurement] The obtained composition for forming a hard coat layer was applied using a bar coater No. 9 onto a 50 μm-thick light-transmitting film (easy-adhesive PET film (Toray Industries, Inc.: Lumirror U403) with a transmittance of 80% or more at 380 nm) and dried at 100°C for 2 minutes in a hot air oven, and then irradiated with ultraviolet light at 400 mJ / cm using a high-pressure mercury lamp with an output of 80 w / cm. 2 The coating layer was cured by irradiation to obtain a light-transmitting film and a hard coat film having a hard coat layer. The hard coat film having this hard coat layer was measured for transmittance at 380 nm and 420 nm using a Hitachi High-Tech spectrophotometer "U-4100" placed in a thermo-hygroscopic chamber at 23°C and a relative humidity of 50% (hereinafter 50% RH).
[0107] [a * , b * Measurement of [Transmittance measurement] * , b * A hard coat film for measurement was obtained. Using a spectroscopic haze meter "SH 7000" manufactured by Nippon Denshoku Industries Co., Ltd., installed in a temperature and humidity controlled room at 23°C and 50% RH, the average value of n=3 measurements under a D65 light source was calculated as a * , b * It was decided.
[0108] [Pencil hardness] A hard-coated film for pencil hardness evaluation was obtained in the same manner as in [Transmittance Measurement]. The obtained hard-coated film was cut into a test film having a length of 100 mm and a width of 50 mm. The pencil hardness of the obtained hard coat film was measured using pencils of different hardness according to a test method in accordance with JIS K5400 (1990). ◎: Pencil hardness is 3H or more (excellent) ○: Pencil hardness is H~2H (good) △: Pencil hardness is F (no problem in practical use) ×: Pencil hardness is HB or less (not practical)
[0109] [Adhesion] A hard-coated film for adhesion evaluation was obtained in the same manner as in [Transmittance Measurement]. The surface of the obtained hard-coated film opposite to the surface on which the hard-coated layer was formed was attached to a glass plate via an adhesive layer having a thickness of about 20 μm, and then a cross-cut peel test was performed on the surface of the hard-coated layer according to JIS K5400, and the surface was evaluated according to the following criteria. ◎: Peeling count 0 / 100 (Excellent) ○: Peeling count 1-5 / 100 (good) △: Number of peeled off pieces: 6-20 / 100 (no practical problems) ×: Number of peeled pieces: 21-100 / 100 (not practical)
[0110] [Warp test] A hard coat film for warpage test was obtained in the same manner as in [Transmittance Measurement]. The obtained hard coat film was cut into a length of 100 mm and a width of 50 mm to prepare a test film, which was then left in a constant temperature and humidity chamber at 22° C. and 50% RH for 6 hours. The test film was placed on a horizontal plane, and the distance between both ends in the width direction was measured at both ends of the long sides and at three points in the center using a microgauge, and the average value was calculated. ◎: 40mm or more (excellent) ○: 30mm or more and less than 40mm (good) △: 10mm or more and less than 30mm (no practical problems) ×: Cylindrical or less than 10 mm (not practical)
[0111] [White clarity evaluation] A hard-coated film for evaluating white color clarity was obtained in the same manner as in [Transmittance measurement]. The white color clarity was evaluated by placing the obtained hard-coated film with the hard-coat layer formed side up on a colorimeter calibration plate (CIE Y=94.9, x=0.3135, y=0.3205, hereinafter referred to as the standard plate) manufactured by Konica Minolta, Inc., and visually evaluating the difference in color from the standard plate, and judging according to the following index. ◎: No noticeable difference in color compared to the standard plate (Excellent) ○: Slightly tinted compared to the standard plate (good) △: The color is clearly different from the standard plate, but the color of the standard plate can be confirmed (no problem in practical use) ×: The color is too dark to see the color of the standard plate (not practical)
[0112] [Table 1]
[0113] [Table 2]
[0114] [Table 3]
[0115] As shown in Tables 1 to 3, by using the hard coating agent of the present invention, it is possible to provide a hard coating film having a hard coating layer that protects the display part from external ultraviolet rays due to its high ultraviolet blocking properties, improves white color clarity, improves the efficiency of the display production process due to its low curl properties, and prevents scratches during the display production process due to its high hard coating properties.
Claims
1. A composition for forming a hard coat layer on a light-transmitting film, comprising: The composition comprises an active energy ray-curable component (A), an ultraviolet ray blocking agent (B), a photopolymerization initiator (C), a color tone adjusting agent (D) and a solvent (E), the active energy ray-curable component (A) contains a polyfunctional urethane (meth)acrylate (a1) having six or more (meth)acryloyl groups and a nurate ring skeleton, The active energy ray-curable composition for forming a hard coat layer, wherein the photopolymerization initiator (C) contains an oxime ester derivative.
2. The active energy ray curable component (A) is The active energy ray curable composition for forming a hard coat layer according to claim 1, further comprising a polyfunctional urethane (meth)acrylate (excluding (a1)) (a2) having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000, and another polyfunctional (meth)acrylate (a3).
3. 13. A hard coat film having a hard coat layer formed by curing the active energy ray-curable composition for forming a hard coat layer according to claim 1 on a light-transmitting film.
4. 4. The hard coat film according to claim 3, which has a transmittance (ta) at a wavelength of 380 nm of 3% or less and a transmittance (tb) at a wavelength of 420 nm of 65% or more.
5. L * a * b * In the color system, b * The hard coat film according to claim 4, wherein the refractive index is -1.5 or more and 3.0 or less.
6. L * a * b * In the color system, a * 6. The hard coat film according to claim 5, wherein the refractive index is −2.5 or more and 1.5 or less.
7. 7. An optical laminated electronic device comprising the hard coat film according to claim 3 and other functional layers laminated together.
Citation Information
Patent Citations
Monomer composition for optical material and cured product
JP2003105033A
Curable composition, cured film, organic el display device, liquid crystal display device, touch panel and touch panel display device
JP2016204585A
Active energy ray-curable resin composition and coating agent
JP2018070820A
Hard coat film having ultraviolet absorptivity
JP2009006513A
Surface protection film
JP2016107498A